THE CONDITIONS FOR THE FORMATION OF THE ARCTIC-NORWEGIAN SCHOOL OF CODS FROM THE 1959, 1960 AND 1961 GENERATIONS IN THE FIRST YEAR OF LIFE (Ob Usloviyakh Formirovaniya Arkto-Norvezhskogo Stada Treski Pokolenii 1959, 1960 I 1961 G. na Pervom Godu Zhizni) - Baranenkov,A. S.; Khokhlin,N. S. (1969)
On the basis of investigations conducted in the Norwegian and W. Barents Seas in 1959, 1960 and 1961, a close connection between the development of cods, plankton and hydrological regime of water was established. Variations in the dates of spawning and the quantity of cod depended mainly on the development of plankton, which in turn was affected by climatic and hydrological conditions in the area, namely, the water temperature, salinity and movement. Graphs and tables present and interpret data on these biological and hydrological aspects. (Author) Trans. of Polyarnyi Nauchno-Issledovatelskii Institut Morskogo Rybnogo Khozyaistva i Okeanografii. Trudy (USSR) v16 p195-214 1964, by M. Slessers.